2017
DOI: 10.1016/j.dsr.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Demersal fish assemblages on seamounts and other rugged features in the northeastern Caribbean

Abstract: Recent investigations of demersal fish communities in deepwater (>50 m) habitats have considerably increased our knowledge of the factors that influence the assemblage structure of fishes across mesophotic to deep-sea depths. While different habitat types influence deepwater fish distribution, whether different types of rugged seafloor features provide functionally equivalent habitat for fishes is poorly understood. In the northeastern Caribbean, different types of rugged features (e.g., seamounts, banks, cany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 85 publications
2
40
0
Order By: Relevance
“…The use of underwater vehicles for the study of deep-water fauna has allowed many new insights in several research areas such as deep-water fish behavioral ecology and habitat selection (e.g., Uiblein, 2011;Uiblein et al, 2002Uiblein et al, , 2003Uiblein et al, , 2010, community ecology (e.g., Quattrini et al, 2015Quattrini et al, , 2017Baldwin et al, 2018), and systematics (Baldwin and Robertson, 2013, 2014Baldwin et al, 2016aBaldwin et al, , 2016b. For the genus Neobythites which includes many species that live below 200 m depth, only very few insights from underwatervehicle encounters have been obtained so far.…”
Section: Discussionmentioning
confidence: 99%
“…The use of underwater vehicles for the study of deep-water fauna has allowed many new insights in several research areas such as deep-water fish behavioral ecology and habitat selection (e.g., Uiblein, 2011;Uiblein et al, 2002Uiblein et al, , 2003Uiblein et al, , 2010, community ecology (e.g., Quattrini et al, 2015Quattrini et al, , 2017Baldwin et al, 2018), and systematics (Baldwin and Robertson, 2013, 2014Baldwin et al, 2016aBaldwin et al, , 2016b. For the genus Neobythites which includes many species that live below 200 m depth, only very few insights from underwatervehicle encounters have been obtained so far.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not directly measure this, the enhanced abundance and relative biomass of planktivorous fishes below shallow waters (discussed in the following section), supports this conclusion. Going deeper, discrete environmental conditions at rariphotic depths including lower temperatures and dissolved oxygen levels (see measurements made in the neighboring Bermuda Atlantic Time-series Station -BATS -during the same period as our survey was undertaken; Supplementary Figure S1), both known to influence reef fish structure with depth (Quattrini et al, 2017a), are likely responsible for the distinct fish assemblages present in that zone. Distinct vertical zonation in reef fish assemblages has previously been reported from St. Peter and St. Paul's Archipelago (mid-Atlantic Ridge, Brazil) (Rosa et al, 2016), Bermuda and Curaçao (Pinheiro et al, 2016), Puerto Rico (Bejarano et al, 2014), and Southern California Bight (Love et al, 2009).…”
Section: Fish Assemblage Structure Across a Depth Gradientmentioning
confidence: 99%
“…Additionally, Johns et al [12] recorded the large 2009 Amazon River plume that intruded into the North Eastern Caribbean and noted that larval fish assemblages in the upper 100 m of the water column differed substantially from previous years' observations. Furthermore, Quattrini et al [13] showed that changes in water mass characteristics in the Northeastern Caribbean Sea result in species turnover at different depths associated with such water mass changes and conveys the importance exerted by water mass characteristics in controlling community structure in the region. The VISB is biologically unique because it includes two ecologically significant spawning aggregation areas 12 km South of St. Thomas: the Red Hind Conservation District and Grammanik Bank.…”
Section: Introductionmentioning
confidence: 99%